Pesantren Revitalization as an Effort to Prevent Brain Rot in the Young Generation: A Neurological Approach - Wildan Fahdika Ahmad (ADP Publisher, 2024)
The digital era that triggers excessive social media consumption has given rise to a non-medical term called